MERSIN TOROS MUSEUM YÖRÜK WEAVINGS - Aksoy, Elif; Marchese, Ron (My University, 2021)
Yörük weavings have an important place in Anatolian history and culture. In Anatolian geography, people who migrate according to climatic conditions to feed their animals and accept this mobility as a lifestyle are called Yörük. Sacks, sackcloths, saddles, floor mats and bags made with carpets, rugs, cicim, zili and sumakh techniques woven by nomads form a wide product repertoire. Such items have a number of physical features peculiar to Anatolian peoples. These features are more pronounced among nomadic groups who live their lives as semi-sedentary beings. Yörüks raise sheep and goats to earn a living and meet their needs. Due to the high density of Yörük settlement in Mersin region, the motif, color and composition features found in weavings are very rich. The Toros Yörük Museum, located in Toros district, is a museum that carries the artworks of the Yörük culture to future generations. The aim of this study is to examine the plain weaves found in the Toros Yörük Museum in terms of technique, material, color, composition and size, and to emphasize its importance in the context of Anatolian Turkish culture.
Keywords: Mersin; Plain Weavings; Toros Yörük Museum; Yörüks.